PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS MASALAH DENGAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT DALAM MENUMBUHKAN KEMAMPUAN LITERASI - Suara, Jaka; Suryati, Suryati; Hatimah, Husnul; Salim, Agus (Jurnal Education and Information Technology, 2023)
The aim of this research was to evaluate the form and eligibility of problem base learning module with science technology society approach for science literacy growing that developed. This was research and development with 4-D development model design which consist of 4 phase namely define, design, develop, and disseminate. The research result data was qualitative and quantitative data. Assessment result quantitative data was number while qualitative data was suggestion and comments collected by validation sheet questionnaire. The developed module was validated by expert, practitioner, and learning trial to 10 students. The research result showed that the developed module was eligible for continue to disseminate phase. This was showed by percent of product validation result by expert was 75% (eligible category), by practitioner was 78.49% (eligible category), and students 77.70% (eligible category).